ONLINE LEARNING DIFFICULTIES AS IMPACT OF COVID-19 IN INDONESIA: Received: 09th August 2021; Revised: 29th November 2022, 18th January 2023; Accepted: 20th January 2023 - Nur’amalia, Yanti; Supriatna, Mamat; Ilfiandra, . (PUPIL: International Journal of Teaching, Education and Learning, 2023)
This article aims to analyze student learning difficulties while online learning during the Covid-19 pandemic. The covers the characteristics of high school students learning difficulties in online learning during the Covid-19 pandemic, factors causing learning difficulties during online learning, and student efforts to overcome learning difficulties during online learning. The method is used the literature review method sourced from books on learning difficulties, and the latest research articles on learning difficulties and the impact of online learning during the pandemic. The results showed that the learning difficulties during online learning during the pandemic, namely understanding the material that was less than optimal due to limited interaction with the teacher, the task load given to students in each subject with a short time impact on physical, emotional, cognitive, and mental fatigue. lose students' motivation to learn and made them prone to experience boredom, stress, anxiety, and worries about the future. This can be attributed to students’ lack of effective learning strategies in doing teacher-assigned tasks and lack of effort to understand teacher-provided materials. The benefit of this study is to provide an overview of the learning difficulties experienced by students during online learning while the Covid-19 pandemic.